The prevalence Regarding the Use of Glucagon-like Peptide-1 (GLP-1) Agonists as an Obesity Treatment among Adult Patients at King Abdulaziz University Medical Services Center, Jeddah, Saudi Arabia: a Descriptive Cross-Sectional Study: The prevalence of Glucagon-like Peptide-1 (GLP-1) Agonists use as an Obesity Treatment among adults in Saudi Arabia. - Alsieni, Mohammed; Babader, Raghad; Kenany, Shahad; Abdulgader, Shahad; Alafif, Raneem; Alahmadi, Atheer; Aloufi, Albatool; Fallatah, Eman; AlQahtani, Rawyah; Izaldin, Alyaa (Journal of King Abdulaziz University: Medical Sciences, 2024)
Background: Glucagon-like peptide-1 (GLP-1) receptor agonists are effective to achieve and sustain body weight reductions in obese individuals. Objectives: To assess the prevalence of GLP-1 agonists used for weight management and associated adverse effects among adult populations at King Abdulaziz University Medical Services Center, Saudi Arabia. Methods: A cross-sectional study was done at on 188 participants using GLP-1. A questionnaire was used to collect data about participants’ demographics, chronic diseases, smoking, weight, height, family support to lose weight, obesity causes, weight loss attempts, pattern of GLP-1 agonists use, the negative side effects GLP-1 agonists use and patients' satisfaction. Results: The mean age was 46.24 ± 12.78 years, the mean BMI was 34.78 ± 5.3 kg/m2, and 80.9% were obese. The most commonly used GLP-1 agonists were semaglutide (66%), for 86.2% the medication was recommended by a physician and the mean medication use duration was 12.43 ± 14.73 months. The mean number of kilograms lost during treatment was 10.11 ± 6.53 kg, 70.2% had negative side effects with nausea (51.1%) the most common. Of them 65.5% were satisfied and 78.7% would recommend others to use GLP-1. Absence of negative effects was significantly higher among those using the medication for diabetes and weight reduction. Conclusion: GLP-1 receptor agonists are promising agents for the treatment of obesity as the mean weight reduction during the drug use among participants was about 10 kilograms. Despite the side effects, the majority were satisfied with the drug and would recommend others to use it.